Pearl dry particle composition, pearl glaze, pearl glaze tile and preparation method thereof
By using a pearl dry particle composition that has been screened and heated with specific ingredients in the dry particle layer of ceramic tiles, the problems of uneven particle shape and low wear resistance in the dry particle layer of existing ceramic tiles are solved, and the ceramic tiles are realized The ideal suspension performance, flow performance and dispersion performance improve the texture and anti-fouling performance of ceramic tiles.
Patent Information
- Application Number
- CN202411414937.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The dry-grain layer particles of existing ceramic tiles are uneven in shape and have burrs and edges, which leads to the phenomenon of bottom sinking when preparing dry-grain glaze layers, which is uneven in dispersion, affecting the texture and anti-fouling properties of ceramic tiles, and at the same time, the wear resistance is not high.
A pearl dry particle composition is used. Its chemical composition has been screened and contains SiO2, Al2O3, MgO, CaO, Na2O, K2O, BaO, ZnO, PbO, SrO and ZrO2. The particles are rounded through specific heating treatment. Achieve good suspension performance, flow performance and dispersion performance.
The particles in the pearl glaze layer are small and round, with beautiful and delicate feel, glossiness in the range of 10~30°, and ideal mechanical properties and wear resistance.
Smart Images

Figure CN118908574B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a pearl dry particle composition, pearl glaze, pearl glaze ceramic tile and a preparation method thereof. Background Art
[0002] In addition to the decorative and simulation effects, the dry particle layer of ceramic tiles can also improve the anti-slip and wear resistance of the product to a certain extent. According to the different types of additional attributes, the dry particles used in the dry particle layer include shiny dry particles, matte dry particles, hard dry particles, antibacterial dry particles, etc., but currently these dry particles are mainly obtained by direct crushing or grinding with water. Therefore, the product particles generally have different shapes and many burrs and edges. As the size of the particles is smaller, the shape is closer to flakes or strips. It is very easy to sink to the bottom when preparing the dry particle glaze layer, resulting in uneven dispersion or even stratification of dry particles in the dry particle layer, uneven glaze surface and even obvious pits on the surface, which seriously affects the texture and anti-fouling performance of ceramic tiles; on the other hand, the dry particle layer prepared by the current dry particles is not very wear-resistant or has a low hardness. Therefore, even after polishing and de-edging, it will still become angular or even fall off after a period of use. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of the present invention is to provide a pearl dry particle composition. Based on its special composition, the product has ideal suspension performance, flowability and dispersion performance when used in the preparation of pearl glaze layer, and will not sink to the bottom. The pearl dry particle size in the obtained pearl glaze layer is small and round, and it has the advantages of beautiful appearance, soft and delicate surface feel, and no dirt. At the same time, the glossiness of the obtained tile can be guaranteed to be in the range of 10~30°, and it has ideal mechanical properties and good wear resistance.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] A pearl dry particle composition comprises the following chemical components in percentage by weight:
[0006] SiO251.2~59.3%, Al2O314.7~21.3%, MgO1.3~2.7%, CaO5.8~10.8%, Na2O 1.7~2.5%, K2O 4.1~5.0%, BaO1.7~6.2%, ZnO1.1~5.7%, PbO0.01~0.05%, SrO1.6~5.3% and ZrO20.07~0.8%.
[0007] Preferably, the chemical components of the pearl dry particle composition further include Fe2O3 and TiO2, and the sum of their mass percentages is ≤0.3%.
[0008] Preferably, the chemical components of the pearl dry particle composition also include burning reduction.
[0009] The pearl dry particle composition of the present invention selects light chemical components through the screening of chemical composition, which can not only achieve good suspension performance and dispersion performance, but also achieve long-term suspension without precipitation and stratification characteristics when processing and preparing glaze. It can be used after simple stirring and aging, which greatly shortens the process time. At the same time, the product will not have the property of harbouring dirt and grime due to its fine particles. Under the action of specific contents of barium oxide, strontium oxide and zirconium oxide, the ratio of silicon, aluminum, sodium and potassium is adjusted at the same time, and the glaze surface prepared can have the characteristics of high flatness, good anti-fouling effect, high hardness and good wear resistance during use; the pearl dry particle composition can present a matte property and a high sense of fashion.
[0010] Preferably, the sphericity of the pearl dry particle composition is ≥0.5.
[0011] The pearl dry particle composition of the present invention has ideal roundness, which can not only reduce the clogging probability of traditional dry particles during glaze spraying, but also has high flatness and good apparent pearl matte effect after the dry particle layer is prepared.
[0012] Preferably, the pearl dry particle composition comprises the following chemical components in percentage by mass:
[0013] SiO251.2~59.3%, Al2O314.7~18.6%, MgO1.3~2.7%, CaO5.8~10.8%, Na2O 1.7~2.5%, K2O 4.1~5.0%, BaO1.7~6.2%, ZnO1.1~5.7%, PbO0.01~0.05%, SrO1.6~5.3% and ZrO20.07~0.8%.
[0014] In the pearl dry particle composition of the present invention, each chemical component plays an important role. The proportion of SiO2 and Al2O3 and Na2O and K2O can ensure that the product has sufficient wear resistance, and the content of BaO and SiO2 and Al2O3 will affect the antifouling effect of the product; on the other hand, oxides such as BaO, ZrO2, SrO and the like will work together with SiO2 and Al2O3 to affect their glossiness. When the above preferred formula is selected, all aspects of the product performance can be maintained at a high level, especially when the aluminum content is low, the texture and antifouling performance of the product are better.
[0015] Preferably, the pearl dry particle composition comprises the following raw materials in parts by weight:
[0016] 12-17 parts of nepheline, 5-10 parts of dolomite, 5-10 parts of calcite, 29-36 parts of potassium feldspar, 5-10 parts of aluminum oxide powder, 15-20 parts of quartz, 0.1-1 parts of zirconium silicate, 2-7 parts of barium carbonate, 2-7 parts of strontium carbonate, 1-5 parts of zinc oxide and 0.01-0.05 parts of red lead;
[0017] In the pearl dry particle composition of the present invention, a raw material with a high content of potassium feldspar is used and Zr, Sr and Ba elements are compounded, so that the raw material can be quickly melted and rounded on the surface during free fall heating, and the heating uniformity is high, the texture is uniform, and the glossiness is controllable.
[0018] Preferably, the mass content of K2O in the potassium feldspar is ≥10wt%.
[0019] Preferably, the mass content of CaO in the calcite is 50-58wt%.
[0020] Preferably, the nepheline comprises the following chemical components in percentage by mass:
[0021] SiO238~45%, CaO4~9%, K2O10~14% and Na2O3.5~7%.
[0022] Preferably, the dolomite comprises the following chemical components in percentage by mass:
[0023] MgO19~24%, CaO30~35%.
[0024] Preferably, the purity of the strontium carbonate is ≥60wt%.
[0025] Preferably, the purity of the barium carbonate is ≥70wt%.
[0026] Another object of the present invention is to provide a method for preparing the pearl dry particle composition, comprising the following steps:
[0027] The prepared raw materials are mixed, melted at 1480-1580°C, cooled, and crushed to obtain mixed particles A;
[0028] The mixed particles A are crushed to obtain mixed particles B;
[0029] The mixed particles B are heated at 800-1000° C. for 1-4 seconds in a natural falling manner, and cooled to set, thereby obtaining the pearl dry particle composition.
[0030] Compared with the traditional dry granular particles, the pearl dry granular composition of the present invention has a pearl-like round appearance, so it can achieve good suspension performance, flow performance and dispersion performance when glazing, and no precipitation phenomenon occurs. The main reason is that through the rational allocation of chemical composition and the combination of a free-falling specific heating treatment method, after the prepared materials are melted, cooled and crushed to a specific small size, the obtained particles are naturally dropped by free fall, and a specific temperature heating treatment is applied in the process. During the heating process, the appearance of the particles is deformed and begins to be rounded and glossy under the action of gravity. The dry granular composition not only presents an ideal pearl luster and processing performance, but also has a higher stacking density and smaller gaps between particles after glazing due to its roundness, and the obtained glaze surface is smoother and has a better anti-fouling effect. However, in the process of product preparation, the chemical composition of the mixed particles B and the heating time and temperature during natural falling are very critical. The main reason is that these two key factors, in addition to determining the appearance roundness, glossiness, and suspension of the obtained pearl dry particle composition, are also closely related to the hardness and wear resistance of the pearl dry particle composition. If the selected preparation raw materials are inappropriate, resulting in inappropriate chemical composition of the prepared mixed particles B, or if the heating time is too long or too short, the appearance performance, processing performance and use performance of the pearl dry particle composition cannot be taken into account.
[0031] Preferably, the raw material preparation is carried out in a frit furnace when preparing the mixed particles A.
[0032] More preferably, the frit furnace comprises a heating furnace, a water tank, a collecting basket and a draining platform.
[0033] More preferably, the heating furnace is provided with an outflow port, the outflow port is connected to a water tank, and the water tank is provided with a water pipe connected to cooling water.
[0034] More preferably, after mixing, the prepared raw materials are first placed into a heating furnace in a frit furnace through a feeder to melt to form a molten liquid, and then flow into a water tank through an outflow port of the heating furnace, and a water pipe is opened to allow cooling water to pass through to cool the molten liquid, and the molten liquid is water quenched and crushed to form mixed particles A, which are then collected through a collecting basket and drained on a draining platform.
[0035] Preferably, the particle size of the mixed particles B is ≤75 μm;
[0036] More preferably, the mixing of the particles B is carried out in a dry particle oven when preparing the pearl dry particle composition.
[0037] More preferably, the dry granulation furnace comprises a hopper, a burner, a granulation blowing air duct, a heating chamber, a cooling air duct and a discharge pipe.
[0038] More preferably, the hopper is connected to the particle blowing duct, the burner is arranged on the heating chamber, the burner is connected to the gas pipeline, the cooling duct is arranged at the lower part of the heating chamber, and the discharge pipe is arranged at the bottom of the heating chamber.
[0039] More preferably, the mixed particles B are first added into a hopper, blown into a heating chamber through a particle blowing duct and fall freely, and the heating chamber is connected to a burner to burn gas to heat the mixed particles B, and then cooling air is introduced into the cooling duct to cool and shape the mixed particles, and the obtained pearl dry particle composition is discharged through a discharge pipe.
[0040] More preferably, the pearl dry particle composition is further treated with iron sieving.
[0041] More preferably, the ventilation pressure of the particle blowing duct is 2800~3200Pa.
[0042] During the free-fall heating process, although the chemical composition of the pearl dry particle composition will not change with the setting of its process conditions, the wind pressure of the blowing duct will affect the concentration and uniformity of the dry particle powder when it falls, and the heating uniformity will be different, and even affect the residence time of the powder in the heating chamber (i.e., the heating time), so it will also affect the appearance of the prepared pearl dry particle composition, and ultimately lead to different suspension performance and light transmission performance. After optimization, the use of the wind pressure in the above range can ensure that the dry particles are evenly heated during the free-fall heating process, and have an ideal processing effect.
[0043] More preferably, the heating chamber is cylindrical, with a height of 6 to 12 m and a cylinder diameter of 1.5 to 3 m. The number of the burners is 3 to 18. The cooling air ducts are arranged at the lower part of the burners, and the number of the cooling air ducts is 3 to 6.
[0044] By controlling the height of the heating chamber, the duration of the heating process of the mixed particles B and the temperature zone distribution can be effectively adjusted.
[0045] It should be noted that the burner of the heating chamber of the present invention can be provided with multiple layers, or can be arranged in a herringbone shape, and the number can be 3 to 18, which is mainly determined by the total amount and frequency of the mixed particles B to be processed, as well as the heating temperature and combustion efficiency during heating. Those skilled in the art can adjust it randomly, as long as the mixed particles B can be effectively heated in the heating chamber to make their surface rounded, and the final pearl dry particle composition can obtain the expected effect. Similarly, the cooling air duct can be distributed around the lower part of the heating chamber, or can be arranged in multiple layers, or in a herringbone shape. The main function of the cooling air duct is to help the pearl dry particle composition to quickly cool and shape, while maintaining the pressure in the heating chamber. Therefore, those skilled in the art can adjust the distribution according to actual needs, and no mandatory requirements are made.
[0046] Another object of the present invention is to provide a pearl glaze comprising the pearl dry particle composition of the present invention.
[0047] Another object of the present invention is to provide a pearl glaze tile, comprising the pearl glaze of the present invention.
[0048] Preferably, the ceramic tile comprises a body layer, a surface glaze layer, a printing layer and a pearl glaze layer which are connected in sequence, and the pearl glaze layer comprises the pearl glaze described in the present invention.
[0049] Preferably, the surface glaze layer comprises the following chemical components in mass percentage: SiO2 61~62.9%, Al2O3 19.6~22.5%, MgO 1.4~3.0%, CaO 1.1~2.6%, Na2O 2.9~3.6%, K2O 2.2~2.7%, and ZrO2 1.2~9.7%.
[0050] Preferably, the chemical composition of the surface glaze layer also includes Fe2O3 and TiO2, and the sum of the mass percentages of the two is ≤0.5%;
[0051] Preferably, the composition of the surface glaze layer also includes loss on ignition, with a mass percentage of 0.8-1.7%.
[0052] More preferably, the glaze layer comprises the following raw materials in parts by weight:
[0053] 18-23 parts of potassium feldspar, 25-31 parts of sodium feldspar, 4-8 parts of calcined talc, 2-6 parts of wollastonite, 6-10 parts of quartz, 2-15 parts of zirconium silicate, 14-21 parts of calcined kaolin, 3-7 parts of air knife clay, 1-5 parts of aluminum oxide, 0.1-0.5 parts of sodium carboxymethyl cellulose, 0.1-0.5 parts of sodium tripolyphosphate and 30-50 parts of water.
[0054] Preferably, at least 100 mL of the glaze is weighed and passed through a 100-mesh sieve, and then 100 mL of the sifted liquid is passed through a 325-mesh sieve, and the weight of the residue after drying is 0.3-0.5 g.
[0055] When compounding with the pearl glaze layer formed by the pearl dry particle composition of the present invention, in order to ensure the bonding performance between the surface glaze layer and the pearl glaze layer and the appearance effect presented after the bonding, the particle size of the surface glaze layer needs to be maintained at a smaller size when preparing the glaze to avoid the pores generated by the accumulation of particles causing interlayer pores or particle translation.
[0056] Preferably, the pearl glaze layer comprises the following raw materials in parts by weight:
[0057] 40-60 parts of suspending agent and 20-30 parts of pearl dry particle composition;
[0058] More preferably, the method for preparing the pearl glaze ceramic tile comprises the following steps:
[0059] Arranging a green body layer and spraying water on the green body layer;
[0060] The raw materials for preparing each surface glaze layer are prepared into a surface glaze material, and then poured on the body layer to form the surface glaze layer;
[0061] Constructing a printing layer by inkjet printing on the glaze layer;
[0062] The raw materials for preparing each pearl glaze layer are prepared into a pearl dry granule glaze, and then poured on the printed layer to form a pearl glaze layer to obtain a blank to be fired;
[0063] The blank to be fired is fired at 1200-1220°C and edge-ground to obtain the pearl glaze tile.
[0064] More preferably, the specific gravity of the glaze during pouring is 1.85-1.95 g / mL, the flow rate is 33-38 s / g, and the total pouring amount is 55-75 g.
[0065] More preferably, when pouring the pearl dry particle glaze, the specific gravity of the pearl dry particle glaze is 1.12-1.20 g / mL, the flow rate is 33-38 s / g, and the total pouring amount is 50-60 g.
[0066] At the same time, it should be noted that the pearl dry particle composition of the present invention is not limited to the above scheme when preparing the glaze and the pearl glaze. Based on the diversification of the material system, the pearl glaze layer of the present invention can also be prepared using other raw materials. For example, the pearl glaze layer can also be prepared using the following raw materials:
[0067] Preferably, the pearl glaze layer comprises the following raw materials in parts by weight:
[0068] 80-110 parts of pearl dry particle composition, 0.1-0.5 parts of sodium carboxymethyl cellulose, 0.1-0.5 parts of sodium tripolyphosphate and 30-50 parts of water.
[0069] Accordingly, the construction of the pearl glaze layer may also be different.
[0070] More preferably, the method for preparing the pearl glaze ceramic tile comprises the following steps:
[0071] Arranging a green body layer and spraying water on the green body layer;
[0072] The raw materials for preparing each surface glaze layer are prepared into a surface glaze material, and then poured on the body layer to form the surface glaze layer;
[0073] Constructing a printing layer by inkjet printing on the glaze layer;
[0074] The raw materials for preparing each pearl glaze layer are prepared into a pearl dry granule glaze, and then a part of the pearl dry granule glaze is sprayed on the printing layer in advance, and then the remaining pearl dry granule glaze is poured on the printing layer to form a pearl glaze layer, thereby obtaining a blank to be fired;
[0075] The blank to be fired is fired at 1200-1220°C and edge-ground to obtain the pearl glaze tile.
[0076] More preferably, the specific gravity of the pearl dry glaze when spraying the pearl dry glaze is 1.10-1.25 g / mL, and the total spraying amount is 10-20 g. The specific gravity of the pearl dry glaze when pouring the pearl dry glaze is 1.85-1.95 g / mL, and the total pouring amount is 60-70 g.
[0077] Preferably, in the pearl glaze ceramic tile, the glazing amount of pearl glaze is determined according to the specifications of the prepared ceramic tile, and is generally measured using a 400*400 mm disk. The ceramic tile specifications include 600*600mm, 800*800mm, 600*1200mm, 750*1500mm, 800*1600mm, 900*1800mm, 800*2600mm, 1200*1200mm, and 1200*2700mm.
[0078] The ceramic tile of the present invention adopts the special dry particle composition as the pearl glaze layer and is laid on the surface glaze layer and the printing layer, and no additional glaze layer or material layer is set. Based on the rounded appearance and fine particle characteristics of the pearl dry particle composition in the pearl glaze, it not only has a good pearl matte feeling and delicate feel, but also has high laying flatness, high wear resistance under a small friction coefficient, and no tendency to absorb dirt due to gaps or multiphases, and fully meets the anti-fouling standards.
[0079] Preferably, the green body layer comprises the following raw materials in parts by weight:
[0080] 13-18 parts of ball clay, 7-10 parts of sodium stone powder, 20-30 parts of potassium sodium stone powder, 19-25 parts of kaolin, 13-18 parts of raw mud, 6-9 parts of bentonite, 2-4 parts of diopside, 1-3 parts of rotten brick particles, 0.4-0.8 parts of water glass, 0.1-0.4 parts of diluent, 0.2-0.6 parts of green body reinforcing agent, 0.01-0.1 parts of methyl organic matter and 35-45 parts of water.
[0081] The preparation method of the green body layer is as follows: after ball-milling each prepared raw material for 8 hours, the obtained glaze slurry is first passed through an 80-mesh sieve and then through a 250-mesh sieve, and the residue after drying the 250-mesh sieve is qualified if the residue is 2-4% based on dry material, and if it is unqualified, it is re-ball-milled and sieved; the qualified glaze slurry is iron-removed, passed through an 80-mesh sieve, and then placed in a slurry storage tank for aging for 20-30 hours, the obtained slurry is spray-granulated, and the obtained particles are pressed into a green body after aging for 20-30 hours, and the green body layer is obtained by drying.
[0082] The beneficial effects of the present invention are that the present invention provides a pearl dry particle composition. Based on its special component composition, the product has ideal suspension performance, flow performance and dispersion performance when used in preparing a pearl glaze layer, and does not sink to the bottom. The pearl dry particle particles in the obtained pearl glaze layer are small and round, and have the advantages of being beautiful, soft and delicate on the surface, and not hiding dirt. At the same time, the glossiness of the obtained tile can be guaranteed to be within the range of 10-30°, and it has ideal mechanical properties and good wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 This is a schematic diagram of the structure of the molten block furnace described in Example 1 of the present invention, wherein: a screw feeder 1, a hopper 2, a heating furnace 3, a smoke extraction hole 4, a combustion-supporting air hole 5, a flamethrower 6, a molten pool 8, an outflow port 9, a water trough 10, a water pool 11, a water pipe 12, a molten liquid fluid 13, a collecting basket 14, a coolant 15, a feeder drive motor 16, a reduction mechanism 17, molten block particles 18, a draining platform 19, a draining platform water trough 20, and a fire hole 31.
[0084] Figure 2 It is a schematic structural diagram of the dry granule furnace described in Example 1 of the present invention, wherein: a dry granule furnace 21, a granule blowing air duct 22, a hopper 23, mixed particles B24, a smoke exhaust duct 25, a cooling air duct 27, and a discharge port 28.
[0085] Figure 3 This is a schematic diagram of the pearl glaze tile described in Example 1 of the present invention.
[0086] Figure 4 It is a schematic diagram of different days of standing experiment of the pearl dry particle composition described in Example 1, Example 7, Comparative Example 1 and Comparative Example 2 in Effect Example 1 of the present invention after being prepared into slurry.
[0087] Figure 5 This is a comparison chart of the effects of the pearl glaze ceramic tile before and after cleaning during the cleanability test of Example 2 of the present invention.
[0088] Figure 6 This is a schematic diagram of the pearl glaze ceramic tile described in Example 2 of the present invention.
[0089] Figure 7 This is a schematic diagram of the ceramic tile described in Comparative Example 1 of the present invention.
[0090] Figure 8 This is a comparison chart of the cleaning performance of the ceramic tile described in Comparative Example 5 of the present invention before and after cleaning. DETAILED DESCRIPTION
[0091] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0092] Example 1
[0093] An embodiment of a pearl dry particle composition, pearl glaze, pearl glaze tile and a preparation method thereof according to the present invention, wherein the pearl dry particle composition comprises the following preparation steps:
[0094] (1) The raw materials are pre-mixed in a mixer and then Figure 1 The screw feeder 1 of the frit furnace shown is transferred to the heating furnace 3, melted at 1520°C into a molten liquid and flows through the outflow port 9 to the water tank 10 below. The formed molten liquid fluid 13 is flushed into the cooling water through the water pipe 12 provided in the water tank 10 for cooling and quenching. The obtained particles flow to the water pool 11 and the crushed frit particles 18 are collected by the collecting basket 14. After being loaded, they are transferred to the drainage platform 19. The drainage platform water tank 20 provided on the platform allows the drained water to flow back into the water pool. The drained particles are the mixed particles A.
[0095] (2) crushing the mixed particles A by a crusher to obtain mixed particles B, wherein the particle size of the mixed particles B is ≤75 μm,
[0096] (3) Transfer the mixed particles B to Figure 2 The hopper 23 of the dry granule furnace 21 is shown, and then the granule is blown into the heating chamber through the blowing granule duct 22 with a wind pressure of 3000Pa connected to the hopper and falls freely. The heating chamber is cylindrical, with a height of 10m and a cylinder diameter of 2m. The fuel gas is introduced into the heating chamber through the burner 26 to burn and heat so that the temperature in the furnace reaches 800~1000℃, so the mixed granules B are heated for 1~4s during the falling process; then the granules obtained by the heating treatment are cooled and shaped through the cooling duct 27 with a wind pressure of 2000Pa, and finally discharged through the discharge port 28, and the iron is removed to obtain the pearl dry granule composition. The sphericity of the pearl dry granule composition is 0.6~0.8.
[0097] The preparation raw materials are: 14.6 parts of nepheline, 6.77 parts of dolomite, 7.43 parts of calcite, 32.33 parts of potassium feldspar, 8.09 parts of aluminum oxide powder, 17.21 parts of quartz, 0.1 parts of zirconium silicate, 4.99 parts of barium carbonate, 5.44 parts of strontium carbonate, 3.02 parts of zinc oxide and 0.02 parts of red lead.
[0098] Wherein, the mass content of K2O in the potassium feldspar is 20wt%;
[0099] The mass content of Cao in the calcite is 55wt%.
[0100] The nepheline comprises the following chemical components in percentage by mass:
[0101] SiO240%, CaO5%, K2O12% and Na2O5%.
[0102] The dolomite comprises the following chemical components in percentage by mass:
[0103] MgO20%, CaO32%.
[0104] The purity of the strontium carbonate is 80wt%.
[0105] The purity of the barium carbonate is 85wt%.
[0106] The chemical composition of the pearl dry particle composition is shown in Table 1.
[0107] The pearl dry particle composition is applied to prepare pearl glaze and pearl glaze ceramic tile, and the steps are as follows:
[0108] (1) Arrange a green body layer and spray 16±1g of water on the green body layer to make it wet;
[0109] The green body layer includes the following preparation raw materials:
[0110] 15.6 parts of ball clay, 8.5 parts of sodium stone powder, 25.3 parts of potassium sodium stone powder, 22.7 parts of kaolin, 15.8 parts of raw mud, 7.3 parts of bentonite, 2.7 parts of diopside, 2.1 parts of rotten brick particles, a total of 100 parts of dry materials, plus 0.46 parts of water glass, 0.27 parts of diluent, 0.37 parts of green body reinforcing agent, 0.05 parts of methyl organic matter and 40 parts of water;
[0111] The preparation method of the green body layer is as follows: each prepared raw material is put into a ball mill for 8 hours, 140g of the obtained glaze slurry is taken and passed through an 80-mesh sieve and then a 250-mesh sieve, until the residue after passing the 250-mesh sieve is 2-4% after drying, which is qualified based on dry material; then the slurry is put into a slurry storage tank for iron removal and passed through an 80-mesh sieve for aging for 24 hours, the slurry after aging and mixing enters a spray tower for granulation, the powder particles after granulation are transported to a powder bin for aging for 24 hours, the powder particles are transported to a press to be pressed into a green body, the green body enters a drying kiln at 150°C for drying for 50 minutes, and the green body layer is obtained when the green body exits the drying kiln;
[0112] (2) preparing the raw materials for each surface glaze layer into a surface glaze, and then pouring it on the green body layer to construct the surface glaze layer. The specific gravity of the surface glaze when pouring the surface glaze is 1.90 g / mL, the flow rate is 35 s / g, and the total pouring amount is 70±1 g;
[0113] The raw materials for preparing the surface glaze layer are 20 parts of potassium feldspar, 28 parts of sodium feldspar, 6 parts of calcined talc, 3 parts of wollastonite, 8 parts of quartz, 10 parts of zirconium silicate, 17 parts of calcined kaolin, 5 parts of air knife clay, 3 parts of aluminum oxide, 0.15 parts of sodium carboxymethyl cellulose, 0.35 parts of sodium tripolyphosphate, and 40 parts of water;
[0114] When preparing the glaze, the materials are mixed and then ball-milled to a qualified fineness. The qualified fineness requirement is: at least 100 mL of the material is pre-screened through a 100-mesh sieve, and then 100 mL of the sieved liquid is screened through a 325-mesh sieve. The residue is dried and weighed to be 0.3-0.5 g.
[0115] (3) inkjet printing is performed on the glaze layer to construct a printing layer;
[0116] (4) preparing raw materials for each pearl glaze layer into a pearl dry granule glaze, and then pouring it on the printed layer to form a pearl glaze layer to obtain a blank to be fired;
[0117] The specific gravity of the pearl dry glaze when pouring the pearl dry glaze is 1.15 g / mL, and the total pouring amount is 53±1 g;
[0118] The pearl dry particle glaze is obtained by mixing 50 parts of a suspending agent and 25 parts of a pearl dry particle composition and stirring for 30 minutes, and then passing through a 100-mesh sieve;
[0119] The suspending agent is F310 produced by Taishan Defu Technology Co., Ltd.
[0120] (5) The blank to be fired is fired at 1200-1220°C for 36 minutes and the edges are ground to obtain the pearl glaze tile.
[0121] The ceramic tile of Example 1 is made by using a composite process of a suspension agent and a pearl glaze layer, and the glaze surface presents a soft light granular shape, and the effect is as follows: Figure 3 As shown, this type of product can be used directly as a finished product, or it can be further polished by brush polishing, soft polishing, high-gloss polishing, etc. to make the surface particles present different light sensations.
[0122] Example 2
[0123] An embodiment of a pearl dry particle composition, pearl glaze, pearl glaze tile and a preparation method thereof according to the present invention is different from Embodiment 1 only in that the preparation method of the pearl glaze tile is:
[0124] (1) Arrange a green body layer and spray 16±1g of water on the green body layer to make it wet;
[0125] (2) preparing the raw materials for each surface glaze layer into a surface glaze, and then pouring it on the green body layer to construct the surface glaze layer. The specific gravity of the surface glaze when pouring the surface glaze is 1.90 g / mL, the flow rate is 35 s / g, and the total pouring amount is 60±1 g;
[0126] (3) inkjet printing is performed on the glaze layer to construct a printing layer;
[0127] (4) preparing raw materials for each pearl glaze layer into a pearl dry glaze, then spraying a portion of the pearl dry glaze on the printed layer using a 0.52 mm spray gun, and then pouring the remaining pearl dry glaze on the printed layer to form a pearl glaze layer, thereby obtaining a blank to be fired;
[0128] The specific gravity of the pearl dry glaze when spraying the pearl dry glaze is 1.20 g / mL, and the total spraying amount is 15±1 g. The specific gravity of the pearl dry glaze when pouring the pearl dry glaze is 1.90 g / mL, and the total pouring amount is 67±1 g.
[0129] The pearl dry particle glaze comprises the following raw materials in parts by weight:
[0130] 100 parts of pearl dry particle composition, 0.15 parts of sodium carboxymethyl cellulose, 0.35 parts of sodium tripolyphosphate and 40 parts of water;
[0131] The pearl dry particle glaze is obtained by mixing various raw materials, ball-milling them to a qualified fineness, and then passing through a 100-mesh sieve. The qualified fineness requirement is: at least 100 mL of the material is pre-screened through a 100-mesh sieve, and 100 mL of the sieved liquid is screened through a 325-mesh sieve. The residue is dried and weighed to be 0.3-0.5 g.
[0132] (5) The blank to be fired is fired at 1200-1220°C for 36 minutes and the edges are ground to obtain the pearl glaze tile.
[0133] Example 3
[0134] An embodiment of a pearl dry particle composition, pearl glaze, pearl glaze tile and a preparation method thereof according to the present invention is different from embodiment 2 only in that:
[0135] The raw materials for preparing the pearl dry particle composition are: 17 parts of nepheline, 5 parts of dolomite, 5 parts of calcite, 36 parts of potassium feldspar, 5 parts of aluminum oxide powder, 20 parts of quartz, 1 part of zirconium silicate, 2 parts of barium carbonate, 7 parts of strontium carbonate, 1.95 parts of zinc oxide and 0.05 parts of red lead;
[0136] The chemical composition of the pearl dry particle composition is shown in Table 1.
[0137] Example 4
[0138] An embodiment of a pearl dry particle composition, pearl glaze, pearl glaze tile and a preparation method thereof according to the present invention is different from embodiment 2 only in that:
[0139] The raw materials for preparing the pearl dry particle composition are: 12 parts of nepheline, 10 parts of dolomite, 10 parts of calcite, 32.99 parts of potassium feldspar, 5 parts of aluminum oxide powder, 15 parts of quartz, 1 part of zirconium silicate, 7 parts of barium carbonate, 2 parts of strontium carbonate, 5 parts of zinc oxide and 0.01 parts of red lead;
[0140] The chemical composition of the pearl dry particle composition is shown in Table 1.
[0141] Example 5
[0142] An embodiment of a pearl dry particle composition, pearl glaze, pearl glaze tile and a preparation method thereof according to the present invention is different from embodiment 2 only in that:
[0143] The raw materials for preparing the pearl dry particle composition are: 14.87 parts of nepheline, 7 parts of dolomite, 9 parts of calcite, 29 parts of potassium feldspar, 10 parts of aluminum oxide powder, 18 parts of quartz, 0.1 parts of zirconium silicate, 6 parts of barium carbonate, 5 parts of strontium carbonate, 1 part of zinc oxide and 0.03 parts of red lead;
[0144] The chemical composition of the pearl dry particle composition is shown in Table 1.
[0145] Example 6
[0146] An embodiment of a pearl dry particle composition, pearl glaze, pearl glaze tile and a preparation method thereof according to the present invention is different from embodiment 2 only in that:
[0147] The raw materials for preparing the pearl dry particle composition are: 17 parts of nepheline, 6.2 parts of dolomite, 5 parts of calcite, 32.33 parts of potassium feldspar, 10 parts of aluminum oxide powder, 15 parts of quartz, 1 part of zirconium silicate, 4.99 parts of barium carbonate, 5.44 parts of strontium carbonate, 3 parts of zinc oxide and 0.04 parts of red lead;
[0148] The chemical composition of the pearl dry particle composition is shown in Table 1.
[0149] Example 7
[0150] An embodiment of a pearl dry particle composition, pearl glaze, pearl glaze tile and a preparation method thereof according to the present invention is different from embodiment 2 only in that:
[0151] The wind pressure of the particle blowing duct in the dry particle furnace 21 is 2800 Pa, and the sphericity of the obtained pearl dry particle composition is 0.6-0.8.
[0152] Example 8
[0153] An embodiment of a pearl dry particle composition, pearl glaze, pearl glaze tile and a preparation method thereof according to the present invention is different from embodiment 2 only in that:
[0154] The wind pressure of the particle blowing duct in the dry particle furnace 21 is 3200 Pa, and the sphericity of the obtained pearl dry particle composition is 0.6-0.8.
[0155] Comparative Example 1
[0156] A dry granular composition and a tile prepared therefrom, the difference from Example 2 is only that:
[0157] The dry granular composition comprises the following preparation steps:
[0158] (1) The raw materials are pre-mixed in a mixer and then Figure 1 The screw feeder 1 of the frit furnace shown is transferred to the heating furnace 3, melted at 1520°C into a molten liquid and flows through the outflow port 9 to the water tank 10 below. The formed molten liquid fluid 13 is flushed into the cooling water through the water pipe 12 provided in the water tank 10 for cooling and quenching. The obtained particles flow to the water pool 11 and the crushed frit particles 18 are collected by the collecting basket 14. After being loaded, they are transferred to the drainage platform 19. The drainage platform water tank 20 provided on the platform allows the drained water to flow back into the water pool. The drained particles are the mixed particles A.
[0159] (2) The mixed particles A are crushed by a crusher to obtain a dry particle composition, wherein the particle size of the dry particle composition is ≤75 μm, and the raw materials for preparing the dry particle composition are the same as those of the pearl dry particle composition in Example 2; the chemical composition of the dry particle composition is the same as that in Example 2.
[0160] Comparative Example 2
[0161] A dry granular composition and a tile prepared therefrom, the difference from Example 2 is only that:
[0162] The dry granular composition comprises the following preparation steps:
[0163] (1) The raw materials are pre-mixed in a mixer and then Figure 1 The screw feeder 1 of the frit furnace shown is transferred to the heating furnace 3, melted at 1520°C into a molten liquid and flows through the outflow port 9 to the water tank 10 below. The formed molten liquid fluid 13 is flushed into the cooling water through the water pipe 12 provided in the water tank 10 for cooling and quenching. The obtained particles flow to the water pool 11 and the crushed frit particles 18 are collected by the collecting basket 14. After being loaded, they are transferred to the drainage platform 19. The drainage platform water tank 20 provided on the platform allows the drained water to flow back into the water pool. The drained particles are the mixed particles A.
[0164] (2) The mixed particles A are crushed by a crusher to obtain a dry particle composition, wherein the particle size of the dry particle composition is 106 μm. The raw materials for preparing the dry particle composition are the same as those of the pearl dry particle composition in Example 2. The chemical composition of the dry particle composition is the same as that in Example 2, and the subsequent steps are the same as those in Example 2.
[0165] Comparative Example 3
[0166] A pearl dry particle composition, pearl glaze and ceramic tile prepared therefrom, which differs from Example 2 only in that:
[0167] The raw materials for preparing the pearl dry particle composition are: 35 parts of potassium feldspar, 8 parts of sodium feldspar, 8 parts of kaolin, 15 parts of barium carbonate, 6 parts of wollastonite, 5 parts of zinc oxide, 6 parts of strontium carbonate, 11 parts of calcite, 2 parts of quartz and 4 parts of aluminum oxide.
[0168] The pearl dry particle composition comprises the following preparation steps:
[0169] (1) The raw materials are pre-mixed in a mixer and then Figure 1 The screw feeder 1 of the frit furnace shown is transferred to the heating furnace 3, melted at 1450°C into a molten liquid and flows through the outflow port 9 to the water tank 10 below. The formed molten liquid fluid 13 is flushed into the cooling water through the water pipe 12 provided in the water tank 10 for cooling and quenching. The obtained particles flow to the water pool 11 and the crushed frit particles 18 are collected by the collecting basket 14. After being loaded, they are transferred to the drainage platform 19. The drainage platform water tank 20 provided on the platform allows the drained water to flow back into the water pool. The drained particles are the mixed particles A.
[0170] (2) crushing the mixed particles A by a crusher to obtain mixed particles B, wherein the particle size of the mixed particles B is ≤75 μm;
[0171] (3) Transfer the mixed particles B to Figure 2 The mixed particles B are placed in the hopper 23 of the dry granule furnace 21 shown in the figure, and then blown into the heating chamber through the blowing granule duct 22 with a wind pressure of 3000Pa connected to the hopper and fall freely. The heating chamber is cylindrical, with a height of 10m and a cylinder diameter of 2m. Gas is introduced into the heating chamber through the burner 26 for combustion and heating so that the temperature in the furnace reaches 800-1000°C. Therefore, the mixed particles B are heated for 1-4s during the falling process; the particles obtained by the heating treatment are then cooled and shaped through the cooling duct 27 with a wind pressure of 2000Pa, and finally discharged through the discharge port 28, and iron is removed to obtain the pearl dry granule composition;
[0172] The chemical composition of the pearl dry particle composition is shown in Table 1.
[0173] Comparative Example 4
[0174] A pearl dry particle composition, pearl glaze and ceramic tile prepared therefrom, which differs from Example 2 only in that:
[0175] The raw materials for preparing the pearl dry particle composition are: 35 parts of potassium feldspar, 8 parts of sodium feldspar, 8 parts of kaolin, 15 parts of barium carbonate, 6 parts of dolomite, 5 parts of zinc oxide, 6 parts of strontium carbonate, 11 parts of calcite, 2 parts of quartz and 4 parts of aluminum oxide.
[0176] The pearl dry particle composition comprises the following preparation steps:
[0177] (1) The raw materials are pre-mixed in a mixer and then Figure 1 The screw feeder 1 of the frit furnace shown is transferred to the heating furnace 3, melted at 1450°C into a molten liquid and flows through the outflow port 9 to the water tank 10 below. The formed molten liquid fluid 13 is flushed into the cooling water through the water pipe 12 provided in the water tank 10 for cooling and quenching. The obtained particles flow to the water pool 11 and the crushed frit particles 18 are collected by the collecting basket 14. After being loaded, they are transferred to the drainage platform 19. The drainage platform water tank 20 provided on the platform allows the drained water to flow back into the water pool. The drained particles are the mixed particles A.
[0178] (2) crushing the mixed particles A by a crusher to obtain mixed particles B, wherein the particle size of the mixed particles B is ≤75 μm;
[0179] (3) Transfer the mixed particles B to Figure 2 The mixed particles B are placed in the hopper 23 of the dry granule furnace 21 shown in the figure, and then blown into the heating chamber through the blowing granule duct 22 with a wind pressure of 3000Pa connected to the hopper and fall freely. The heating chamber is cylindrical, with a height of 10m and a cylinder diameter of 2m. Gas is introduced into the heating chamber through the burner 26 for combustion and heating so that the temperature in the furnace reaches 800-1000°C. Therefore, the mixed particles B are heated for 1-4s during the falling process; the particles obtained by the heating treatment are then cooled and shaped through the cooling duct 27 with a wind pressure of 2000Pa, and finally discharged through the discharge port 28, and iron is removed to obtain the pearl dry granule composition;
[0180] The chemical composition of the pearl dry particle composition is shown in Table 1.
[0181] Comparative Example 5
[0182] A pearl dry particle composition, pearl glaze and ceramic tile prepared therefrom, which differs from Example 2 only in that:
[0183] The raw materials for preparing the pearl dry particle composition are: 12 parts of nepheline, 5 parts of dolomite, 5 parts of calcite, 30.86 parts of potassium feldspar, 15 parts of aluminum oxide powder, 25 parts of quartz, 0.1 parts of zirconium silicate, 2 parts of barium carbonate, 2 parts of strontium carbonate, 3 parts of zinc oxide and 0.04 parts of red lead;
[0184] The chemical composition of the pearl dry particle composition is shown in Table 1.
[0185] Comparative Example 6
[0186] A pearl dry particle composition, pearl glaze and ceramic tile prepared therefrom, which differs from Example 2 only in that:
[0187] The raw materials for preparing the pearl dry particle composition are: 21 parts of nepheline, 4.9 parts of dolomite, 5 parts of calcite, 40 parts of potassium feldspar, 5 parts of aluminum oxide powder, 15 parts of quartz, 0.1 parts of zirconium silicate, 3 parts of barium carbonate, 2 parts of strontium carbonate, 3 parts of zinc oxide and 1 part of red lead;
[0188] The chemical composition of the pearl dry particle composition is shown in Table 1.
[0189] Comparative Example 7
[0190] A pearl dry particle composition, pearl glaze and ceramic tile prepared therefrom, which differs from Example 2 only in that:
[0191] The wind pressure of the particle blowing duct in the dry particle furnace 21 is 1000 Pa, and the sphericity of the obtained pearl dry particle composition is less than 0.5.
[0192] Comparative Example 8
[0193] A pearl dry particle composition, pearl glaze and ceramic tile prepared therefrom, which differs from Example 2 only in that:
[0194] The wind pressure of the particle blowing duct in the dry particle furnace 21 is 5000 Pa, and the sphericity of the obtained pearl dry particle composition is less than 0.5.
[0195] The chemical composition of the pearl dry particle composition is shown in Table 1. Since the chemical composition of the pearl dry particle composition used in Example 2, Examples 7-8, Comparative Examples 1-2 and Comparative Examples 7-8 is the same as that in Example 1, they are not shown one by one. In addition, the loss on ignition is not included in Table 1.
[0196] Table 1
[0197]
[0198] Effect Example 1
[0199] In order to verify the processing performance of the pearl dry particle composition of the present invention, the pearl dry particle composition / dry particle composition prepared in each embodiment and comparative example was prepared into a slurry according to the following method, and then placed at room temperature and pressure for 10 days. The slurry was illuminated with light every day for the first 5 days and on the 10th day to observe whether it sank to the bottom and was layered, and whether there was a difference in light transmittance between the top and bottom parts:
[0200] 25 parts of the pearl dry particle composition / dry particle composition and 50 parts of the suspending agent (with the same composition as in Example 2) were mixed and stirred for 30 minutes, and then passed through a 100-mesh sieve to obtain a slurry.
[0201] The observation results are shown in Table 2 and Figure 4 shown.
[0202] It can be seen from the results that the pearl dry particle composition prepared by the present invention has ideal suspension performance and dispersion performance. After being processed into glaze slurry by using a suspending agent, it can remain non-stratified and non-precipitated for a long time, and there is almost no difference in the light transmittance of the glaze at the top and bottom. It can be prepared in advance under certain circumstances without being prepared and used immediately. The processing performance is excellent, especially better than the dry particle composition products obtained in Comparative Examples 1 and 2 that have not undergone free-fall rounding treatment. In addition, according to Example 1, Examples 7-8 and Comparative Examples 7-8, it can be clearly seen that during the rounding treatment, the wind pressure of the blowing duct has different effects on the rounding effect. When the wind pressure is too low, the dry particles are easy to agglomerate during the rounding process, and the heating is uneven, resulting in that some dry particles cannot be rounded and the sphericity is low. Therefore, the suspension performance is not ideal and the light transmittance is not uniform. When the wind pressure is too high, the dry particles may partially hit the furnace wall during the blowing process, thereby accelerating the fall, so the heating uniformity is also not high, showing a similar result to that of too low wind pressure.
[0203] Table 2
[0204]
[0205] In addition, the glossiness of the ceramic tile products of each embodiment and comparative example was tested using a WGG60-E4 photometer in accordance with ISO-2767 and GB8941.2. The results are shown in Table 3.
[0206] Table 3
[0207]
[0208] It can be seen that the glossiness of the product of the present invention is basically in the range of 10~30°, showing a pearl-like matte effect with excellent natural feel, while some products in the comparative examples cannot achieve a similar effect.
[0209] Effect Example 2
[0210] In order to verify the various properties of the ceramic tile of the present invention, the ceramic tiles prepared in the embodiments and comparative examples were subjected to the following tests:
[0211] (1) Texture test: 10 testers were selected to touch each product and rate its texture (blindfolded). The score ranged from 1 to 10 (integer points). The finer the texture, the higher the score, and the rougher the texture, the lower the score. The average score of each sample was calculated and recorded.
[0212] (2) Antifouling performance test: The antifouling grade test was conducted in accordance with GB / T 3810.14-2016. The green pollutant in light oil, the red pollutant in light oil, iodine solution and olive oil were used as pollutants. The lowest grade among the test results of each pollutant was used for statistics.
[0213] (3) Cleanability test: Use blue anti-fouling test blue, purple-blue ink, blue and black oil-based markers to draw pictures and lines on the surface of the tile within a range of 100×100mm, then leave it for 24 hours, wet it with a sponge and rinse it with tap water for 3 minutes, then wipe it with a towel to observe whether the traces left after wiping are obvious and how easy it is to wipe.
[0214] (4) Wear resistance test: According to GB / T 3810.14-2016 Part 7 Determination of surface wear resistance of glazed tiles, the test sample is 100×100 mm, and 8 different sample positions are sampled for each example. The test results are comprehensively judged.
[0215] The test results are shown in Table 4.
[0216] Table 4
[0217]
[0218] It can be seen from the results that the ceramic tile prepared by the pearl dry particle composition of the present invention has an ideal fine texture, antifouling effect and wear resistance. At the same time, the ceramic tile is very easy to clean. After being painted with a marker, it can be wiped clean without using a large force, and no obvious traces remain. In addition, the matte effect presented by the pearl glaze layer in the ceramic tile makes the product have a high sense of fashion. Among them, the formula ingredients of the products of Examples 2 to 4 are further preferred, the aluminum content is lower, the texture of the product is better, and the antifouling level is higher. Figure 5 As shown, after the product of Example 2 was marked with pictures and lines and cleaned, there was almost no obvious residual trace on the surface of the pearl glaze tile. In contrast, the dry granular composition in Comparative Example 1 was not subjected to free-fall heating treatment, and the particles were not round. The tiles obtained in Example 2 and Comparative Example 1 were compared, as shown in FIG. Figure 6 and 7As shown, the products of this type in Comparative Example 1 can be seen to have obvious roughness and wrinkles on the plane, and the flatness is low. Therefore, the texture of the product of Comparative Example 1 is poor, and its gloss is also dim under the same preparation process. The dry granular composition prepared by the product described in Comparative Example 2 has slightly larger particles. Although the texture is slightly improved, it is still not as good as the product of the embodiment; Comparative Examples 3 and 4 are round bead dry particles prepared using similar raw materials in the prior art, but the BaO content of the dry granular composition in Comparative Example 3 is too high, and the dirt absorption is increased, while the silicon and aluminum contents are low, the wear resistance of the fired glaze becomes low, and pinhole defects are also prone to increase the dirt absorption. Therefore, although the texture of the product is good, its anti-fouling effect is poor and the wear resistance level is low; the product of Comparative Example 4 is prepared on the basis of the product of Comparative Example 3. The raw materials are adjusted and some dolomite is introduced. The anti-fouling performance and cleaning performance of the product are improved, but the wear resistance is still not improved. The formula types used in the preparation of the dry granular composition in Comparative Examples 5 and 6 are the same as those of the example products, but the silicon and aluminum components in the product of Comparative Example 5 are too much, which will lead to a decrease in the antifouling performance of the product. Figure 8 As shown, there are still obvious residual traces on the product after wiping, while the excessive sodium and potassium components in the product of Comparative Example 6 will lead to poor wear resistance of the product, which fully illustrates that even if similar raw material formulas and processes are selected, if the formula ratio is improperly adjusted, the chemical composition of the obtained dry granular composition may be improper, and the texture, antifouling performance and wear resistance of the product cannot be taken into account.
[0219] On the other hand, according to Example 1, Examples 7-8 and Comparative Examples 7-8, it can be seen that in the preparation process of the pearl dry particle composition, if the blowing air pressure during the free fall heating process is improperly set, the sphericity of the obtained pearl dry particle composition is not high. In addition to affecting the suspension performance and processing performance of the product as mentioned above, it will also seriously affect the texture of the obtained tile. The result is similar to the product of Comparative Example 1 which is not subjected to the free fall heating rounding treatment.
[0220] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A pearl dry particle composition, characterized in that: The chemical composition includes the following mass percentages: SiO251.2~59.3%, Al2O314.7~21.3%, MgO1.3~2.7%, CaO5.8~10.8%, Na2O1.7~2.5%, K2O4.1~5.0%, BaO1.7~6.2%, ZnO1.1~5.7%, PbO0.01~0.05%, SrO1.6~5.3% and ZrO20.07~0.8%; The pearl dry particle composition comprises the following raw materials in parts by weight: 12-17 parts of nepheline, 5-10 parts of dolomite, 5-10 parts of calcite, 29-36 parts of potassium feldspar, 5-10 parts of aluminum oxide powder, 15-20 parts of quartz, 0.1-1 parts of zirconium silicate, 2-7 parts of barium carbonate, 2-7 parts of strontium carbonate, 1-5 parts of zinc oxide and 0.01-0.05 parts of red lead; The method for preparing the pearl dry particle composition comprises the following steps: The prepared raw materials are mixed, melted at 1480-1580°C, cooled, and crushed to obtain mixed particles A; The mixed particles A are crushed to obtain mixed particles B; the particle size of the mixed particles B is ≤75 μm; The mixed particles B are heated in a dry particle furnace at 800-1000° C. for 1-4 seconds in a natural falling manner, and cooled to set, thereby obtaining the pearl dry particle composition; The preparation of raw materials is carried out in a frit furnace when preparing mixed particles A; The frit furnace comprises a heating furnace, a water tank, a collecting basket and a draining platform; The dry granule furnace comprises a hopper, a burner, a granule blowing air duct, a heating chamber, a cooling air duct and a discharge pipe; The heating chamber is cylindrical, with a height of 6-12m and a cylinder diameter of 1.5-3m; the wind pressure of the particle blowing air duct is 2800-3200Pa.
2. A pearl glaze, characterized in that: The invention comprises the pearl dry particle composition as claimed in claim 1.
3. A pearl glaze tile, characterized in that: It comprises a body layer, a surface glaze layer, a printing layer and a pearl glaze layer connected in sequence, wherein the pearl glaze layer comprises the pearl glaze according to claim 2.
4. The pearl glaze tile according to claim 3, characterized in that: The pearl glaze layer comprises the following raw materials in parts by weight: 40-60 parts of suspending agent and 20-30 parts of the pearl dry particle composition.
5. The pearl glaze tile according to claim 3, characterized in that: The pearl glaze layer comprises the following raw materials in parts by weight: 80-110 parts of the pearl dry particle composition, 0.1-0.5 parts of sodium carboxymethyl cellulose, 0.1-0.5 parts of sodium tripolyphosphate and 30-50 parts of water.
6. The method for preparing pearl glaze ceramic tile according to claim 4, characterized in that: The following steps are involved: Arranging a green body layer and spraying water on the green body layer; The raw materials for preparing each surface glaze layer are prepared into a surface glaze material, and then poured on the body layer to form the surface glaze layer; Constructing a printing layer by inkjet printing on the glaze layer; The raw materials for preparing each pearl glaze layer are prepared into a pearl dry granule glaze, and then poured on the printed layer to form a pearl glaze layer to obtain a blank to be fired; The blank to be fired is fired at 1200-1220° C. and edge-ground to obtain the pearl glaze tile.
7. The method for preparing pearl glaze ceramic tile according to claim 5, characterized in that: The following steps are involved: Arranging a green body layer and spraying water on the green body layer; The raw materials for preparing each surface glaze layer are prepared into a surface glaze material, and then poured on the body layer to form the surface glaze layer; Constructing a printing layer by inkjet printing on the glaze layer; The raw materials for preparing each pearl glaze layer are prepared into a pearl dry granule glaze, and then a part of the pearl dry granule glaze is sprayed on the printing layer in advance, and then the remaining pearl dry granule glaze is poured on the printing layer to form a pearl glaze layer, thereby obtaining a blank to be fired; The blank to be fired is fired at 1200-1220°C and edge-ground to obtain the pearl glaze tile.
Citation Information
Patent Citations
Pearl glaze, glazed tile with pearl luster and preparation method of glazed tile
CN118063096A
Colored sand centrifugal granulation device
CN217855999U